2017
DOI: 10.5455/aim.2017.25.156-162
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Implementation of a Heart Failure Telemonitoring System

Abstract: Introduction:The aim of this study was to identify patients at-risk, enhancing self-care management of HF patients at home and reduce the disease exacerbations and readmissions.Method:In this research according to standard heart failure guidelines and Semi-structured interviews with 10 heart failure Specialists, a draft heart failure rule set for alerts and patient instructions was developed. Eventually, the clinical champion of the project vetted the rule set. Also we designed a transactional system to enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…We also verified that ICT promote self-efficacy in patients with rheumatic disease [18], which is reflected in increased confidence and ability to perform daily activities, with reduced pain and increased functional capacity [22]. The majority of previous studies with ICT have demonstrated positive changes in health status, and sometimes increase quality of life in patients with crhonic diseases [22] which corroborates a study that we selected [19]. Also, describing that ICT increased the opportunities to patients for accessing information that disease's self-management [15], [16], [17], [18], [19], the management of symptoms, the identification of exacerbations and therapeutic management [15], [16], [19].…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…We also verified that ICT promote self-efficacy in patients with rheumatic disease [18], which is reflected in increased confidence and ability to perform daily activities, with reduced pain and increased functional capacity [22]. The majority of previous studies with ICT have demonstrated positive changes in health status, and sometimes increase quality of life in patients with crhonic diseases [22] which corroborates a study that we selected [19]. Also, describing that ICT increased the opportunities to patients for accessing information that disease's self-management [15], [16], [17], [18], [19], the management of symptoms, the identification of exacerbations and therapeutic management [15], [16], [19].…”
Section: Resultssupporting
confidence: 85%
“…We verified that the ICT's were identical in the different studies, the web intervention provided throughout the informative platforms and of registration as well as of e-learning where the more evidenced. It was possible to identify that the ICT's have positive effects in the patients with chronic diseases, which was verified that these have effects in the promotion of self-care and in selfmanagement of their health [15], [16], [17], [18], [19]. One of the results of the studies was the improvement of the overall increase of the patient's heath status, linked with a bigger knowledge and information about the control of symptoms and therapeutic regime [16] that allowed a better selfmanagement of their condition, decreasing the visits to the hospital [15].…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Several of these studies demonstrated usability and potential efficacy for improving HF outcomes. Evidence shows that few mHealth apps are under development in countries such as Russia [57] and Iran [58]. Given the global public health burden of HF, large-scale studies to test these mHealth apps or systems for efficacy is warranted in America and around the world.…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, the implementation of this technology as a platform for post-acute care has been less addressed. It has received more attention in the management of chronic diseases such as heart disease [ 23 ] or diabetes self-care [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%